PERANAN PENDIDIKAN SEBAGAI TRANSFORMASI BUDAYA - Sopan Adrianto (CKI ON SPOT, 2019)
Education is a process of civilizing humans so education is very important for the transfer of culture. Education aims to build the totality of human capabilities, both as individuals and members of society. As a vital element in civilized human life, culture takes its constituent elements from all the sciences which are considered truly vital and are very necessary in interpreting everything in their lives. Humans who do not know culture are not the same as their own people. Therefore we mustpreserve and preserve culture by means of the educational process including cultural elements. So cultural elements should be included in the education process so that output from education is not only knowledge but is ready to live in society